Effects of the Supplementation a Lipid Emulsion Diet of Tetraselmis suecica for Juvenile Tapes Philippinarum - Hasanat, M.A.; Sarker, M.S.A.; Jahan, Parveen; Uddin, Musleh; Lavens, Partick (Asian Journal of Chemistry, 2010)
Hatchery reared juvenile Tapes philippinarum were grown for 4 weeks. T. philippinarum was fed Tetraselmis suecica (T.s.) at a feeding ration of 0.5%, 1.0% and 1.5% algae (dry weight) per wet weight per day. The control diet, a mixture of lsochrysis galbana (Clone T-Iso) and T. suecica (1 : 1 on dry weight basis), is known to support good growth. Tetraselmis suecica is deficient in docasahexaenoic acid (22 : 6 (n-3)) but is rich in ecosephantaenoic acid (20 : 5 (n-3)). The algal diet was supplemented with a DHA-rich emulsion (Em50D) at a concentration of 50% of the dry weight of the algal diet. The growth and fatty acid composition of T. philippinarum were used as parameters to evaluate the effect of the lipid supplementation. The supplementation of emulsion Em50D improved very little the growth of T. philippinarum. From the second week onwards, the growth of T. philippinarum few 0.5% or 1.0% T. suecica with or without lipid supplementation was lower than the growth of the animals fed the control diet. The clam which received an algal diet supplemented with emulsion Em50D had a significant higher lipid content than the animals fed solely on algae. There was no direct relation between the lipid content of the T. philippinarum and it growth. Starved clams lost 30% lipid compared to the control fed algae and 26% of the initial lipid reserves. This result is focused that the supplementation of emulation Em50D, with a DHA content of 45.03%, resulted in a sharp increase of the DHA levels in the clams with 21.88%, 21.19% and 20.29% at a feeding ration of 0.5%, 1.0% and 1.5% respectively. The results suggested that EPA could fulfill the (n-3) HUFA requirements of juvenile T. philippinarum but a mixture of EPA and DHA seemed to be a little better than only EPA.